Sexual Compatibility with Spouse Questionnaire: Development and Psychometric Property Evaluation - Maryam Nekoolaltak; Zohreh Keshavarz; Masoumeh Simbar; Ali Mohammad Nazari; Ahmad Reza Baghestani (Shiraz University of Medical Sciences, 2020)
Background: Sexual compatibility between husband and wife is an effective factor in both sexual and marital satisfaction. However, there is limited valid and reliable questionnaire to measure the degree of sexual compatibility between the couples. Methods: In this exploratory mixed method study, 54 individuals were interviewed in the qualitative phase and 448 persons participated in the quantitative phase. Totally 502 participants (261 woman, 241 men) took part in this study. According to 205 final codes derived from the qualitative phase, 102 initial items were developed, the number of which reached 69 items after deletion and merging performed by the research team. After face validity, content validity and construct validity, 68 items were introduced into the construct validity phase. Results: Following exploratory factor analysis and promax rotation, the items were reduced to 35 in 4 factors: "Requirements of a sexual relationship", "Sexual agreement", "Contextual obstacles" and "Outcomes of sexual compatibility". The questionnaire Cronbach alpha and correlation coefficient of the test-retest method were 0.90 and 0.91, respectively. Conclusion: Final Questionnaire included 35 items in 4 point-Likert scale with total score of between 35-140. This valid and reliable questionnaire is brief, easily interpreted and can  measure the main factors affecting sexual compatibility with the spouse in clinics and research fields.